2006
DOI: 10.1007/bf03344186
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia as the first manifestation of Cushing’s disease

Abstract: A 39-yr-old man presented to our hospital with unexplained erythrocytosis and hypertension. His follow-up for erythrocytosis had begun 2 yr earlier in another hospital and he had been diagnosed with polycythemia rubra vera. On admission to our hospital he was hypertensive (165/95 mmHg) and, except for the presence of moon-like face and facial plethora, his physical examination was normal. His hemoglobin concentration was 19.2 g/dl, and hematocrit was 58.9% with an increased red blood cell mass of 58 ml/kg as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Activation of these pathways cooperates in the generation of stress-specific erythroid progenitors expressing high levels of transforming growth factor β (TGF-β) receptor 3 [72,73]. The clinical patients with gain (Cushing’s syndrome) or loss (Addison’s disease) of GR function develop erythrocytosis or anemia, respectively [74,75] indicated that GR regulates stress erythropoiesis also in man.…”
Section: Different Mechanisms Regulate Recovery From Acute and Chronimentioning
confidence: 99%
“…Activation of these pathways cooperates in the generation of stress-specific erythroid progenitors expressing high levels of transforming growth factor β (TGF-β) receptor 3 [72,73]. The clinical patients with gain (Cushing’s syndrome) or loss (Addison’s disease) of GR function develop erythrocytosis or anemia, respectively [74,75] indicated that GR regulates stress erythropoiesis also in man.…”
Section: Different Mechanisms Regulate Recovery From Acute and Chronimentioning
confidence: 99%
“…While HSPC-specific effects of HPA axis dysregulation have not been directly examined, clinical observations imply an important role for GR in blood homeostasis. Patients with Cushing's disease who overexpress GCs develop erythrocytosis (Gursoy et al, 2006), whereas those with Addison's disease, marked by insufficient GC production, have normocytic anemia (Ellis, 2013). Acute or chronic blood loss (“erythroid stress”) also activates GR to promote erythroblast expansion (Bauer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Harvey Cushing reported that his first patient, Minnie G., presented 5.30!10 12 /l erythrocytes and bright mucosae notwithstanding frequent nose and bowel bleedings (7). More recently, polycythaemia was the presenting feature in two patients with Cushing's disease (8,9). However, a thorough evaluation of RBC counts in patients with Cushing's syndrome and their course after remission of hypercortisolism is yet to be performed.…”
Section: Introductionmentioning
confidence: 99%